ART AS A MEDIUM OF DELIBERATION: A CASE STUDY OF PUBLIC SPACE UTILIZATION BY THE TARING PADI COMMUNITY - Isvara, Aruna Langit; Ismoyo, Sindu Lintang (Arty: Jurnal Seni Rupa, 2025)
This study examines the role of art as a medium of deliberation in public spaces through a case study of the Taring Padi art community in Yogyakarta. Using a qualitative approach and a case study method, the research involved observations, in-depth interviews, and document analysis. Findings reveal that the Taring Padi community utilizes visual arts such as murals, posters, and billboards to voice social, political, and environmental issues, as well as to advocate for public rights. Through collective work, thematic discussions, and collaboration with local communities, the group creates inclusive and democratic public spaces aligned with the principles of deliberative democracy. Art serves not only as an aesthetic expression but also as a catalyst for social change, strengthening solidarity among marginalized communities. This research contributes to the literature on art, public spaces, and democracy by proposing an art-based advocacy model relevant to equitable development.